2021
DOI: 10.3390/nu13020545
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Quality Associated with Self-Reported Diabetes, Osteoarthritis, and Rheumatoid Arthritis among Younger and Older US Adults: A Cross-Sectional Study Using NHANES 2011–2016

Abstract: Background: To date, few studies have compared the dietary quality of US adults with diabetes mellitus (DM), osteoarthritis (OA), and rheumatoid arthritis (RA) by age groups. Methods: This study used cross-sectional data from adult participants from National Health and Nutrition Examination Survey 2011–2016 to identify dietary quality measured by Healthy Eating Index (HEI)-2015 total and component scores and self-reported disease status for DM, OA, and RA. Associations between the disease status and HEI-2015 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
0
10
1
Order By: Relevance
“…Similar results were reported by other authors as well [ 38 , 39 ]. Other studies have mostly reported a different macronutrient distribution compared to our study, including higher energy, carbohydrate, fat, sugar, and arachidonic acid intakes [ 40 , 41 , 42 , 43 , 44 ]. Under-reporting of energy intake and reporting of biased dietary information has been described in individuals with RA, which may have influenced average energy and macronutrient intake [ 38 , 45 ].…”
Section: Discussioncontrasting
confidence: 67%
“…Similar results were reported by other authors as well [ 38 , 39 ]. Other studies have mostly reported a different macronutrient distribution compared to our study, including higher energy, carbohydrate, fat, sugar, and arachidonic acid intakes [ 40 , 41 , 42 , 43 , 44 ]. Under-reporting of energy intake and reporting of biased dietary information has been described in individuals with RA, which may have influenced average energy and macronutrient intake [ 38 , 45 ].…”
Section: Discussioncontrasting
confidence: 67%
“…In a cross-sectional study in Arizona, USA in 2009 with aim of assessing the dietary quality of older women (≥55 years) with RA and healthy controls using the Healthy Eating Index-2005 (HEI-2005), it was shown that patients with RA had signi cantly lower dietary quality (30). In cross-sectional study conducted in 11,768 US adult from National Health and Nutrition Examination Survey 2011-2016 to assay dietary quality measured by Healthy Eating Index (HEI)-2015 and self-reported disease status for RA, showed that a poor overall quality of dietary pattern was related with RA among older adults aged 60 years and older (17). Indeed, it seems that following a healthier dietary pattern could reduce the chance or developing RA.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective cohort of the Nurses' Health Study and the Nurses' Health Study II, with the aim of evaluating the relationship between long-term diet quality, was measured by the 2010 Alternative Healthy Eating Index and the risk of RA in women, it was shown that a healthier diet was associated with a reduced risk of RA (16). In crosssectional study conducted in US adult from National Health and Nutrition Examination Survey 2011-2016 to assay dietary quality measured by Healthy Eating Index (HEI)-2015, it was shown that adherence to a poor quality dietary pattern was related to odds of RA among older adults (17). Previous studies have examined the relationship between HEI and the odds of RA and it should be mentioned that to our knowledge there is no data on the association of the HEI-2015 and RA disease activity.…”
Section: Introductionmentioning
confidence: 99%
“…Three of the included studies in the current systematic review were RCT [23,25,28], three were CT [21,29,30], and the remaining studies were epidemiological. Ten studies referred to RA patients [21][22][23]25,28,[30][31][32][33][34], while two studies [29,31] referred to SpA. One study was an epidemiological design study that used a sample of the general population to identify associations of the combination of diet/nutrition and physical activity with selfreported RA [33].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%